T2 mapping cardiovascular magnetic resonance identifies the presence of myocardial inflammation in patients with dilated cardiomyopathy as compared to endomyocardial biopsy. (10th November 2017) - Spieker, M; Katsianos, E; Gastl, M; Behm, P; Horn, P; Jacoby, C; Schnackenburg, B; Reinecke, P; Kelm, M; Westenfeld, R; Bönner, F
Abstract: Aims: The aim of this study was to determine the value of T2 mapping for the non-invasive assessment of myocardial inflammation in different stages of systolic left ventricular dysfunction in dilated cardiomyopathy (DCM) in comparison with endomyocardial biopsy (EMB). Methods and results: A total of 132 subjects were enrolled between 2013 and 2016 (62 controls and 70 patients with DCM). All patients underwent CMR at 1.5 T and received coronary angiogram and EMB. CMR applied standard protocols including T2 mapping with Gradient And SpinEcho sequence (GRASE). Global T2 relaxation time was significantly increased in patients with DCM compared to the healthy controls (T2 time DCM vs. controls: 65.9 ± 6.2 vs. 60.0 ± 4.2 ms; P  < 0.001). Of note, patients with the presence of inflammatory cells in EMB exhibited further elevation of T2 values (T2 time in patients with the presence of inflammatory cells vs. T2 time in patients without: 68.8 ± 5.8 vs. 64.7 ± 5.9 ms; P  = 0.02). Receiver operating characteristic analysis of our data deciphered a global myocardial T2 time >65.3 ms as the best cut-off for distinction between the healthy controls and patients with myocardial inflammation [sensitivity 93%, specificity 90%, P  < 0.01, area under the curve (AUC) 0.95]. In patients with DCM, this threshold identified patients with biopsy-proven inflammation with a sensitivity of 79% and specificity 58% (AUC 0.72). Conclusion: In patients with DCM and presence of inflammatory cells in the myocardium, myocardial T2 relaxation times may help to non-invasively detect myocardial inflammation. Although there is an overlap of T2 values between patients and healthy controls, T2 mapping may facilitate the identification of patients who may benefit from EMB for therapeutic decision-making.